Synthesis of carbohydrate-derived solid acid catalysts for biodiesel production from palm fatty acid distillate - Ibrahim, Mohd Lokman (2016)
High concerns on the energy security and uncontrolled emissions of greenhouse gas had forced all countries to tum towards the utilization of environmentally-friendly and renewable biofuels. In this work, the usage of inexpensive and non-edible oil feedstock such as palm fatty acid distillate (PF AD) for the biodiesel production is recommended. A highly potential heterogeneous carbon-based solid acid catalyst derived from carbohydrates was successfully developed and applied for biodiesel production. The carbohydrate-derived solid acid catalysts were synthesized by sulfonation of incomplete carbonized carbohydrates using concentrated sulfuric acid. The prepared catalysts underwent a detailed characterization analyses in terms of its active site's functional groups, morphological structure, thermal stability, surface area and density of the acid sites. The catalytic activity of all prepared catalysts had demonstrated the highest conversion of PFAD to biodiesel under the following reaction condition: catalyst loading of 2 wt.%, methanol-to-PFAD molar ratio of 10:1, reaction temperature of75 "C and the reaction time was 3 h. In order to improve the esterification reaction process, an efficient microwave batch reactor was fabricated. A study on a microwave-assisted acceleration of esterification rate of PFAD using glucose-derived solid acid catalyst was carried out. It was found that the radio frequency of microwave energy could enhance the reaction rate faster than the conventional heating technique. The results revealed the potential of microwave irradiation; which offers faster esterification rate with advantages of enhancing the FAME yield and reducing the production cost. Another study was carried out to investigate the effect of high temperature on the esterification reaction of PF AD. The supercritical reactor was used to heat up the reaction system up to sub- and super-critical conditions. The results from the optimization of reaction variables were; reaction temperature of 290 cC, methanol-to- PFAD molar ratio of 6: 1, catalyst amount of 1 wt.% and reaction time of 5 min. The esterification of PFAD in supercritical methanol with the presence of glucose- and starch-derived solid acid catalysts at this condition resulted 95.4% and 97.3% ofF AME yield, respectively - both catalysts yielded significantly higher conversion compared to un-catalyzed supercritical methanol reaction with the ability to be recycled up to 10 times. As a conclusion, it revealed that the sulfonated carbohydrate-derived acid catalysts had high potentials by showing high catalytic activity with better stability and were suitable for the biodiesel production from low-quality feedstock with high FFA content, especially PF AD. The improvement on the reaction rate by applying the invented microwave-assisted and supercritical methanol reactions showed positive outcome - which in tum, proved the fast reaction with high FAME yield.